The therapeutic potential of the novel ribonuclease ranpirnase (Onconase®) in the treatment of malignant mesothelioma - Luciano Mutti; Giovanni Gaudino (Frontiers Media S.A., 2011)
Ribonucleases are a superfamily of RNA-cleaving enzymes that can be cytotoxic since the cleavage of RNA makes its information indecipherable. Ranpirnase is a novel ribonuclease which preferentially degrades tRNA, thus leading to an inhibition of protein synthesis and, ultimately, to cytostasis and cytotoxicity. Ranpirnase has demonstrated antitumor activity both in vitro and in vivo in several tumor models, including malignant mesothelioma. A large phase II trial showed that ranpirnase has diseasemodifying activity against mesothelioma. A first phase III study demonstrated that rampirnase may be combined with doxorubicin and that such an association is more active than Ranpirnase alone against mesothelioma. At present, another large, phase III trial in combination with doxorubicin has completed enrollment and its results are awaited. In all the above studies, ranpirnase died not demonstrate conventional anticancer activity, stabilizing progressive disease and potentially prolonging patients' survival. Finally, a better understanding of its mechanism of action, coupled with its favorable toxicity profile, especially characterized by the lack of major hematologic toxicities, makes ranpirnase an attractive drug to test in combination with other anticancer agents, in MMe as well as in other tumor types.